Criticism and confession: the Bible in the seventeenth century Republic of letters - Hardy, Nicholas (Oxford-Warburg studies, 2017)
Introduction -- Prelude: the discourse of critica in the late Renaissance -- Part I. Debating sacred history in England and the Continent. The 'theological vortex'? Isaac Casaubon in England, 1610-1614 -- Philology divided: the controversy over John Selden's Historie of tithes (1618) -- Conclusion: rethinking historicism -- Part II. Commentary on the New Testament. New Testament scholarship after Scaliger -- Hugo Grotius: 'historical criticism' in its generic and controversial contexts -- Conclusion: the myth of 'critical exegesis' -- Part III. Criticizing the Old Testament. Anti-Protestant controversy and the 'ecclesiastical' versions of the Old Testmanet: the case of Jean Morin -- Protestants and the Septuagint: the failed edition of Patrick Young -- Critical judgement and theological exegesis: the case of Louis Cappel -- Cappel's Critica sacra in the confessional republic of letters -- The London polyglot Bible: synthesis, retrospective, or another controversial intervention? -- Conclusion: from humanistic exegesis to sacred criticism -- Coda: From Critica sacra to enlightened critique?